The Effect of Interest in Learning Mathematics on Mathematics Learning Achievement in Class X SMK Swasta Persiapan Pematangsiantar T.A 2022/2023 - Sembiring, Acloudia Febriani; Manurung, Suprapto; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2022)
Mathematics is one of the subjects that until now students still think mathematics is difficult. This indication can be seen from the low learning achievement of students at the education level so that students' interest in learning mathematics is low. Good mathematics learning achievement will not be achieved optimally if students do not have an interest in learning. The low results obtained in students' mathematics can be seen from the scores obtained by students during learning at school. The purpose of this study was to determine whether there was a positive and significant influence of interest in learning mathematics on mathematics learning achievement of class X students of SMK Swasta Persiapan Pematangsiantar. This study uses this type of quantitative research with Quasi Experimental Design research methods. The population in this study was class X as many as 8 classes in Pematangsiantar Preparation Private Vocational School. The number of samples taken was 30 students, namely class X TBSM-2. Data collection techniques using a questionnaire (Questionnaire) and pre test - post test. The results of the study were to find out how much positive and significant interest in learning mathematics had on mathematics learning achievement for class X students of SMK Swasta Persiapan Pematangsiantar T.A 2022/2023. Questionnaire of interest in learning mathematics in class X belongs to the high category with an average of 72. Learning achievement is based on pre-test and post-test questions with an average score of 62 and 79,6. The results of data analysis show that interest in learning (X) has a positive and significant effect on learning achievement in mathematics (Y) which is indicated by the correlation coefficient value of 0.495. The results of the analysis of determination indicate that the variable of student interest in learning (X) has an effect of 24.5% on the variable of student achievement (Y), while the remaining 75,5% is influenced by internal factors or external factors which were not examined in this study. Because t count 3.168 is greater than t table 2,467, with sig 0.001 so it can be concluded that Ho is rejected and Ha is accepted which means that “There is a positive and significant effect of interest in learning mathematics on mathematics learning achievement in class X SMK Swasta Persiapan Pematangsiantar T.A 2022 /2023.